2014
DOI: 10.3906/bot-1302-55
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin and other factors that promote rooting and sprouting of shoot cuttings in Punica granatum cv. Wonderful

Abstract: The agricultural and medicinal plant pomegranate (Punica granatum L. cv. Wonderful) was studied to examine the effects of wounding of cuttings and to test the effects of different concentrations of indole-3-butyric acid (IBA), gibberellic acid (GA 3 ), hydrogen peroxide (H 2 O 2 ), melatonin (MEL), and ascorbic acid (ASC) on rooting of the shoot cuttings under mist. The data indicated that IBA had a positive influence on the rooting percentage in wounded and nonwounded cuttings. The best rooting was achieved w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 40 publications
2
38
1
1
Order By: Relevance
“…Several studies in mung bean (Li et al ., ), flax (Takáč et al ., ), pomegranate (Sarrou et al ., ) and marigold (Liao et al ., ) have indicated that application of H 2 O 2 may promote AR formation. Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in mung bean (Li et al ., ), flax (Takáč et al ., ), pomegranate (Sarrou et al ., ) and marigold (Liao et al ., ) have indicated that application of H 2 O 2 may promote AR formation. Li et al .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, melatonin functions in plant physiology are being intensively explored. Some evidence implicates its role as a growth stimulator and plant development factor (Hernández-Ruiz et al 2004, 2005Arnao and Hernández-Ruiz 2007;Hernández-Ruiz and Arnao 2008a;Chen et al 2009;Sarrou et al 2014;Zhang et al 2014). It seems that this indoleamine plays a significant role in plant stress defense.…”
Section: Introductionmentioning
confidence: 97%
“…Among many abiotic stresses, melatonin is positively implicated in mitigating plant injury by modulating and promoting the endogenous defense mechanisms against cold , heat , drought , UV light , reactive oxygen species , and osmotic shock . Apart from these defensive roles in plants, melatonin is also known to participate in promoting root formation and seedling growth , as well as plant ripening and the senescence processes . Recently, it was revealed that melatonin acts as a signal molecule for triggering plant defense mechanisms in response to biotic stresses, such as pathogen attacks, by way of the salicylic acid pathway in Arabidopsis , suggesting the pleiotropic roles of melatonin during the entire life cycle of plant growth and development.…”
Section: Introductionmentioning
confidence: 99%